2020
DOI: 10.1101/2020.06.23.20138081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A primary care approach to the COVID-19 pandemic: clinical features and natural history of 2,073 suspected cases in the Corona São Caetano programme, São Paulo, Brazil

Abstract: Background: Despite most cases not requiring hospital care, there are limited community-based clinical data on COVID-19. Methods and findings: The Corona Sao Caetano program is a primary care initiative offering COVID-19 care to all residents of Sao Caetano do Sul, Brazil. After triage of potentially severe cases, consecutive patients presenting between 13th April and 13th May 2020 were tested at home with SARS-CoV-2 reverse transcriptase (RT) PCR; positive patients were followed up for 14 days. RT-PCR-negati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Many studies reported COVID‐19 hospitalizations, but only a few reported the relationship between individuals with obesity and hospitalization. We identified 19 studies that examined the relationship and included them in this analysis 1,28,38,40,44,47–58 . Table S4 presents the results 1,45,47,48,59,60 ; all showed a significantly higher prevalence of individuals with obesity among hospitalized patients than among patients not hospitalized or the general population.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…Many studies reported COVID‐19 hospitalizations, but only a few reported the relationship between individuals with obesity and hospitalization. We identified 19 studies that examined the relationship and included them in this analysis 1,28,38,40,44,47–58 . Table S4 presents the results 1,45,47,48,59,60 ; all showed a significantly higher prevalence of individuals with obesity among hospitalized patients than among patients not hospitalized or the general population.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…All other patients were offered a home visit for self-collection of a nasopharyngeal swab (NPS – both nostrils and throat), which were collected at the patients’ homes under the supervision of trained healthcare personnel. More details can be found in Leal et al(16). Due to shortages of some reagents, two RT-PCR platforms were used at different times during the study: ALTONA RealStar® SARS-CoV-2 RT-PCR Kit 1.0 (Hamburg, Germany) and the Mico BioMed RT-qPCR kit (Seongnam, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…For serology, we tested 10μL of serum or plasma (equivalent in performance) using a qualitative rapid chromatographic immunoassay (Wondfo Biotech Co., Guangzhou, China), that jointly detects anti-SARS172 CoV-2 IgG/IgM. The assay has been found to have a sensitivity of 81.5% and specificity of 99.1% in a U.S. study (16). In our local validation, after two weeks of symptoms, the sensitivity in RT-PCR confirmed cases (N=59) was 94.9%, and specificity in biobank samples (N=106) from 2019 was 100% (16).…”
Section: Methodsmentioning
confidence: 99%
“…We report the clinical characteristics and mortality rates of 23,844 patients diagnosed with COVID-19 in primary care, who constituted 6.84% of the population studied in the Central Catalan Region aged ≥16 years. This is one of only a few larger studies of COVID-19 patients conducted in primary care settings [25,27,28] and the only one to compare the characteristics and risk factors of patients diagnosed with COVID-19 with those of other patients without COVID-19 in the same health care area. Although there is no significant difference in age between patients with and without COVID-19, age is the main factor associated with mortality in patients with COVID-19, along with male sex, diabetes, dyslipidemia and heart failure.…”
Section: Principal Findingsmentioning
confidence: 99%